A lethal legacy - Graham, Heather (Graham, Heather. New York confidential., 2019)
When his cousin's business partner is found dead on an island he inherited, Special Agent Craig Frasier agrees to investigate with psychologist Kieran Finnegan and they discover that the property comes with strange lore and a blood-soaked past.